TCRβ clones in muscle tissue share structural features in patients with idiopathic inflammatory myopathy and are associated with disease activity - Anang, Dornatien C.; Walter, Hannah A. W.; Lim, Johan; Niewold, Ilse T. G.; van der Weele, Linda; Aronica, Eleonora; Eftimov, Filip; Raaphorst, Joost; van Schaik, Barbera D. C.; van Kampen, Antoine H. C.; van der Kooi, Anneke J.; de Vries, Niek (Frontiers in Immunology, 2024)
Objectives: To characterize the T cell receptor (TCRβ) repertoire in peripheral blood and muscle tissues of treatment naïve patients with newly diagnosed idiopathic inflammatory myopathies (IIMs).Methods: High throughput RNA sequencing of the TCRβ chain was performed in peripheral blood and muscle tissue in twenty newly-diagnosed treatment-naïve IIM patients (9 DM, 5 NM/OM, 5 IMNM and 1 ASyS) and healthy controls. Results thereof were correlated with markers of disease activity.Results: Muscle tissue of IIM patients shows more expansion of TCRβ clones and decreased diversity when compared to peripheral blood of IIM as well as healthy controls (both p=0.0001).Several expanded TCRβ clones in muscle are tissue restricted and cannot be retrieved in peripheral blood. These clones have significantly longer CDR3 regions when compared to clones (also) found in circulation (p=0.0002), while their CDR3 region is more hydrophobic (p<0.01). Network analysis shows that clonal TCRβ signatures are shared between patients.Increased clonal expansion in muscle tissue is significantly correlated with increased CK levels (p=0.03), while it tends to correlate with decreased muscle strength (p=0.08).: Network analysis of clones in muscle of IIM patients shows shared clusters of sequences across patients. Muscle-restricted CDR3 TCRβ clones show specific structural features in their T cell receptor. Our results , indicatetand thatindicate that clonal TCRβ expansion in muscle tissue is might be associated with disease activity. Collectively, tThese findings indicate that support a role for specific clonal T cell responses in muscle tissue act as key players in the pathogenesis of the IIM subtypes studied.